Thromboprophylaxis in Neuro Intensive Care Unit - Swain, Amlan; Sahu, Seelora; Panigrahi, Binita; Nag, Deb S. (Journal of Neuroanaesthesiology and Critical Care, 2019)
The propensity for venous thromboembolism in patients admitted to neurocritical care setups is high because of predilection toward venous stasis as well as pathological processes favoring embolus formation and dissemination. The application of routine thromboprophylaxis guidelines in the various subsets of neurologically injured patients is limited by the fear of bleeding inside neurologically significant closed locations. The aim of this review is to lay out thromboprophylaxis guidelines in various subsets of patients admitted to neurocritical care setups according to recent evidence base, which is still an evolving process.
Keywords: thromboprophylaxis; neurocritical care; craniotomy